Foreign Language reading habits among students in Extremadura - Ramón Pérez-Parejo; Álvaro Gutiérrez-Cabezas; José Soto-Vázquez; Francisco Javier Jaraíz-Cabanillas; José Antonio Gutiérrez-Gallego (Ocnos, 2018)
The abundant research work on reading habits in Spain shows a disaggregation of municipalities and cities with little geographical sample of their results. In this way, taking as a starting point previous studies carried out by the Germán Sánchez Ruipérez Foundation in Extremadura in 2007, our work intends to update and extend the data of reading habits by applying them to the contemporary geographical reality and the degree of rurality of the region. Thus, in the context of a survey focused on reading habits in Extremadura responded by 9212 students of all educational levels (Primary, Secondary, University) during 2017, this study exposes and specifically analyzes the data obtained on reading in foreign languages according to the sex, age, level of studies and geographical area of the respondents. We also analyze other variables related to reading in foreign languages that may be significant such as the language, the fact that the school is following a bilingual programme and the average of books read in other languages by immigrant students.